Does Financial Development Reduce Emissions? The Role of Renewable Energy. Evidence from High-Governance Economies - Azizov, Abboskhan (International Journal of Energy Economics and Policy, 2026)
Financial development represents an increasingly recognized yet empirically contested mechanism for addressing climate change. This study investigates the relationship between financial sector deepening and carbon dioxide emissions in sixty high-governance countries from 1995 to 2019. Employing dynamic generalized method of moments estimation, we find that a one percent increase in financial development growth reduces CO2 emission growth by 3.30 percent, while renewable energy expansion contributes an additional 1.74 percent reduction. These effects remain robust across alternative specifications and estimation techniques. The negative relationship emerges specifically in countries with strong institutional frameworks, suggesting that governance quality conditions whether financial systems channel capital toward environmentally beneficial investments. Our findings indicate that financial sector policies represent viable complements to traditional environmental regulations in well-governed economies, demonstrating compatibility between financial deepening and climate mitigation under strong governance conditions.